A three dimensional multiphysics model of a solid oxide electrochemical cell: A tool for understanding degradation. (5th July 2018) - Navasa, Maria; Graves, Christopher; Chatzichristodoulou, Christodoulos; Løye Skafte, Theis; Sundén, Bengt; Lund Frandsen, Henrik
Abstract: Mitigating degradation is essential for extending the lifetime of solid oxide electrochemical cells (SOCs). The conditions leading to degradation, e.g. overpotentials, gas partial pressures, thermal gradients are hard, if not impossible, to retrieve experimentally. Thus, to deconvolute the response from cell testing, modeling can be applied to understand the degradation phenomena in greater detail. Modeling of SOCs is well developed. For computational efficiency, the electrodes are often represented with a mathematical abstraction of zero thickness layer. In this work, further attention is given to the local conditions in the through-thickness of the electrodes, by rigidly integrating classical electrochemistry into a three dimensional multiphysics model of an SOC. Hereby, local conditions (e.g. overpotential) vary through the electrode, and with the coupling to the different transport phenomena occurring (mass, current, momentum and species), this becomes available in three dimensions, throughout a cell. To investigate the validity of the model, a high number of experiments are conducted at different operating conditions, i.e. in both fuel cell and electrolysis mode of operation with H 2 / H 2 O as feedstock varying parameters such as temperature, gas flows and gas compositions. Highlights: A 3D multiphysics model of a SOC is presented. The model allows calculation of local partial pressures distributions in the cell. Overpotential distributions through the electrodes are calculated. Temperature distributions across the cell are also presented. The model is validated against experiments at different operating conditions.